Las Leyes de enseñanza secundaria promulgadas durante el Franquismo (1938-1953) (2014)
This article is the product of a research about legislation in secondary school during Franco’s times, in order to provide valuable information about the genesis and development of a new secondary school system which was growing with the enactment of laws 1938 and 1953 and the role of women within this educational level. This research focuses on two main axes: one of historical and other education, assessing the in‑uence of dictatorial politics and gender segregation that sets a new educational system in Spain. The method used in this research has been the historical comparative analysis and supplemented by some quantitative analysis. To obtain a historical interpretation from a disciplinary perspective, other disciplinary sciences to history of education, such as sociology and statistical sciences have been used. The findings show the political-patriotic and religious character that the public school system takes, along with the disappearance of the model of coeducation. The appearance of modernity that they tried to give to the 1953  Act  did  not  prevent  the  Falange  and  the  Church from maintaining a determining role at this educational level. Eorts of having women in a second place in society were postponed due to economic development, from the Fifties, which boosted an unusually high number of female teachers and students in the institutes that came to be named as “Enseñanza Media”.